Seawater : (The Open University, Walton Hall, 1997)
'Seawater' has been substantially updated in this second edition to take account of recent developments in marine science. Sections dealing with difficult physical and chemical concepts have been developed on the basis of feedback from the first edition, making this an ideal learning tool for oceanography students.